Single-center prospective study on thyroid function outcomes and neurological prognoses at 3 years of age in children with mild neonatal hyperthyrotropinemia - Guoyu Sun; Rui Zhang; Jianing Zhang; Yanxia Zhou; Zezhong Tang; Lili Liu; Xinlin Hou (Frontiers in Endocrinology)
ObjectiveTo explore early management strategies for full-term neonates with TSH 5–10 mU/L and normal FT4.MethodsIn this single-center longitudinal prospective study, 88 neonates diagnosed at 7–14 days were followed to age three.Results94.3% (83/88) had transient TSH elevation; 77 normalized within two months without treatment, while six received levothyroxine (3–5µg/kg/day). Five neonates (5.7%) exhibited persistent hyperthyrotropinemia and had significantly higher initial TSH. No hyperthyroidism was observed. Following up to 3 years old, only one child (1/81, 1.2%) exhibited development delay in personal-social development. Neonates with transient hyperthyrotropinaemia scored higher in problem-solving and personal–social domains than those with persistent hyperthyrotropinaemia. Neonatal FT4 at 7–14 days, timing of TSH normalization, and maternal early-pregnancy FT4 influenced the neurodevelopment of neonates. Infants of mothers with gestational diabetes scored lower in the personal–social domain.ConclusionsPersistent hyperthyrotropinemia occurs in 5.7% of mild cases and is associated with higher initial TSH. Levothyroxine at 3–5 µg/kg/day is both adequate and safe. The majority of neonates got a normal neurodevelopment by age 3, and the subtle difference between transient and persistent hyperthyrotropinemia was impacted by both maternal and neonatal factors.